Code Switching and Code Mixing Uttered by Thai Students in Indonesia: Types and Contributing Factors - Tanzil Huda; Yayah Ikhda Nevia; Nurhayatee Mushoma (Journey: Journal of English Language and Pedagogy, 2025)
Bilingualism and multilingualism are closely related to these language phenomena i.e. code switching and code mixing. Recently, bilingualism and multilingualism are also linked to translingualism This study explores the use of code switching and code mixing among Thai students at Universitas Muhammadiyah Jember in Indonesia, examining their types and underlying causes.. The research, conducted from September 2024 to February 2025, utilized a qualitative descriptive method, gathering data through audio recordings, interviews, and observations. The findings revealed three types of code switching: tag-switching (50%), intra-sentential (40%), and inter-sentential (10%). Similarly, three types of code mixing were identified: alternation (52%), insertion (41.5%), and congruent lexicalization (6%). The study also found that factors such as language proficiency, academic year, social environment, communicative intent, and emotional factors influenced students' language practices. Older cohorts tended to use more Indonesian and English, while newer students relied more on Thai and Malay. The study concludes that code switching and code mixing serve as adaptive strategies for Thai students to navigate their multilingual environment, improve communication, and express their identity. These findings contribute to understanding multilingual practices among international students and support the integration of translanguaging pedagogies in multicultural educational settings.